The festival relationships of the kingdom of Guatemala (1663-1814): The construction of the corpus - Sánchez Mora, Alexander (2020)
This article offers an inventory of the Baroque festivals of the ancient kingdom of Guatemala, which ranged from the Mexican states of Chiapas to the present Republic of Costa Rica, from 1663 to 1814. With this, an attempt is made to correct the situation of widespread ignorance about this literary genre that predominates among researchers in the area, while promoting the study of this long textual tradition.